On borders, border regions and cross-border retail-trading - Kovács, András (Univerzita Pardubice, 2013)
In my study after introducing some basic border-theories, I will focus on an economic-related issue that has hardly been researched until nowadays: cross-border retail trade. In the theoretical part of this paper I aim to highlight the multiple interpretations and explanations of borders. After determination of some basic concepts about socio-economic borders, I introduce a new model about classification of borderland areas in which I determine 4 types of “border spaces”. Following the results of latest border research agendas, I draft a new model, where the typology of cross-border factor flows and their influencing factors are introduced. Here I distinguish 3 ranges of cross-border economic flows, and 5 factors that influence these. In the final part I analyse the most important findings in the field of cross-border retail trade. After distinguishing the terms “shopping tourism” and “cross-border retail trade” (from the point-of-view of the participants, aims, affected area, etc.) I present some empirical evidences about the importance and relevance of cross-border retailing related to the Western part of the Slovakian-Hungarian border area. I focus on the activity of small and medium sized retailers, and on the shopping behaviour of people living in the border area.
Keywords: border; cross-border retail trade; shopping behaviour; Slovakian; Hungarian